2019
DOI: 10.31744/einstein_journal/2020ao4920
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rectovaginal colonization by group B Streptococcus in pregnant women seen at prenatal care program of a health organization

Abstract: Objective: To evaluate the prevalence of group B Streptococci in pregnant women of a corporate health program, as well as the epidemiological correlations. Methods: This retrospective study used medical records of patients who participated of the prenatal care program at a private hospital in the city of São Paulo (SP), Brazil, from 2015 to 2016. Those who abandoned the program or had incomplete data in their medical records were excluded. Quantitative variables were described by means, standard deviations, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
2
0
0
2
Order By: Relevance
“…The examination of GBS colonization data across the five hospitals revealed an overall rate of 21.70% which was similar to average rates in international research (Edwards et al, 2019;Jisuvei et al, 2020;Ramesh Babu et al, 2017;Szylit et al, 2020) and consistent with results of previous Australian studies (Braye et al, 2019;Furfaro et al, 2019;Moorhead et al, 2019). No studies were located to relate findings of the current study in relation to the different models of care (non-and midwifery led care).…”
Section: Gbs Colonizationsupporting
confidence: 88%
“…The examination of GBS colonization data across the five hospitals revealed an overall rate of 21.70% which was similar to average rates in international research (Edwards et al, 2019;Jisuvei et al, 2020;Ramesh Babu et al, 2017;Szylit et al, 2020) and consistent with results of previous Australian studies (Braye et al, 2019;Furfaro et al, 2019;Moorhead et al, 2019). No studies were located to relate findings of the current study in relation to the different models of care (non-and midwifery led care).…”
Section: Gbs Colonizationsupporting
confidence: 88%
“…Furthermore, we observed that primiparas who had a preterm delivery more often received antibiotic prophylaxis due to the colonization of the genital tract by Streptococcus agalactiae. This is consistent with the findings by Szylit et al, who reported that primiparas were more frequently positive for Streptococcus agalactiae [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…A caracterização das gestantes com colonização por EGB foi semelhante a apresentada em outro estudo que encontrou maior positividade entre gestantes com idade de 26 a 35 anos, em 'outro estado civil', não tabagistas nem etilistas, com um parceiro sexual e gravidez não programada (24) . Outro estudo realizado também em São Paulo não mostrou associação entre fatores de risco socioeconômicos, ponderais ou demográficos e a colonização vaginal pelo EGB (12) .…”
Section: Pesquisa Realizada Pelo Centers Forunclassified
“…No Brasil, existem poucos trabalhos que evidenciam a prevalência da colonização por EGB em gestantes. Em estudo retrospectivo realizado em São Paulo com 287 gestantes, 67 apresentaram resultado positivo para estreptococo do grupo B, o que correspondeu a prevalência de 23,3% (12) .…”
Section: Introductionunclassified